Telltale Women : Chronicling Gender in Early Modern Historiography - Meyer, Allison Machlis (Book collections on Project MUSE., 2021)
"In Telltale Women Allison Machlis Meyer challenges established perceptions of source study, historiography, and the staging of gender politics in well-known drama, arguing that narrative historiographers frequently value women's political interventions and use narrative techniques to invest women's voices with authority, while dramatists reshape this source material to create stage representations of royal women that condemn queenship and female power"--